Small‐size printed coupled‐fed antenna for eight‐band LTE/GSM/UMTS wireless wide area network operation in an internal mobile handset. Issue 6 (1st April 2013) - Ban, Yong‐Ling; Chen, Jin‐Hua; Li, Joshua Le‐Wei; Wu, Yujiang
Abstract : A simple small‐size printed antenna for eight‐band long‐term evolution (LTE)/GSM/UMTS wireless wide area network operation in an internal mobile handset application is proposed. Occupying a compact size of 15 × 40 mm 2 on the ungrounded region of the system circuit board and a low profile of 4 mm, the presented antenna is a coupled‐fed configuration. With the longer branch of the feeding strip, a λ /4 resonant mode at around 2.7 GHz can be obtained to cover the desired LTE2500 operation. A fundamental λ /4 resonant mode over the desired lower band of LTE700/GSM850/900 can also be generated at 750 MHz by the long meandered coupling strip (length of about 113 mm). Moreover, two additional higher‐order resonant modes at around 1.75 and 2.25 GHz can also be obtained by the coupling strip. By including a chip inductor L at the feeding point, the impedance matching over the lower and upper bands can be improved in order to achieve the two wide operating bands of 698–960 and 1710–2690 MHz. With the following properties of small size, ease of fabrication and good radiation characteristics, the proposed antenna is a good candidate for the fourth LTE mobile phone applications.